2010
DOI: 10.1007/s10508-010-9598-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Consequences of Casual Online Sexual Activities on Heterosexual Relationships: A U.S. Online Survey

Abstract: Some researchers have illustrated how the Internet can provide users with an ideal atmosphere to explore sexuality; however, most have stressed the Internet’s negative impact on intimate relationships. Notably, much of this research has focused on the small minority of men who compulsively engage in online sexual activities (OSA), overlooking the majority of men and women who use OSA recreationally (either individually or with a partner). Addressing these limitations, data on heterosexual adults in committed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
75
0
12

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 26 publications
5
75
0
12
Order By: Relevance
“…Like individuallevel results, some research on couples has shown pornography use to have positive correlates. Grov et al (2011) found that when viewed together aspartners,pornography usewasassociated with increases in sexual frequency, a willingness to try new sexual behaviors, and less boredom with sex. Couples who utilized pornography together also found it easier to discuss sexual wants and fantasies with their partners (Daneback, Traeen, & Månsson, 2009).…”
Section: Individual and Relational Correlates Of Pornography Usementioning
confidence: 99%
See 1 more Smart Citation
“…Like individuallevel results, some research on couples has shown pornography use to have positive correlates. Grov et al (2011) found that when viewed together aspartners,pornography usewasassociated with increases in sexual frequency, a willingness to try new sexual behaviors, and less boredom with sex. Couples who utilized pornography together also found it easier to discuss sexual wants and fantasies with their partners (Daneback, Traeen, & Månsson, 2009).…”
Section: Individual and Relational Correlates Of Pornography Usementioning
confidence: 99%
“…At the individual level, higher rates of pornography use have been found to be associated with greater levels of depressionamongmen(Bridges&Morokoff,2011),morenegative feelingsaboutromanticpartners (Grov,Gillespie,Royce,&Lever, 2011), and engagement in risky sexual behaviors (Sinkovic, Stulhofer, & Bozic, 2012). This research is partially countered by research which has suggested that pornography exposure may be related to increased sexual knowledge and openness for some individuals (Lofgren-Mårtenson & Månsson, 2010;Weinberg, Williams, Kleiner, & Irizarry, 2010).…”
Section: Individual and Relational Correlates Of Pornography Usementioning
confidence: 99%
“…they experience sexual arousal (Paul, 2009;Shaughnessy et al, 2011), improve their sex life, gain sexual knowledge, change attitudes towards sex and life in general (Hald & Malamuth, 2008), and enrich their real-life sexual contacts (Grov, Gillespie, Royce & Lever, 2011). While the negative impact of pornography on opposite gender role-models (Barak, Fisher, Belfry & Lashambe, 1999), sexual socialization (Stulhofer, Busko & Landripet, 2010), and partnerships (Whitty & Quigley, 2008) has also found its introduction into (Internet) pornography literature, there are several cybersex specific negative consequences discussed.…”
Section: Introductionmentioning
confidence: 99%
“…32 Nonetheless, not all online interactions are detrimental to romantic relationships. 33,34 For example, Grov and colleagues 35 showed that moderate or light amounts of online sexual activities can yield relationship benefits, including increases in the quality and frequency of sex, and greater intimacy with the primary partner. This seems to depend on the agreements conveyed in the relationship and on what role technologymediated behaviors play in the relationship.…”
mentioning
confidence: 99%